Collaborative Governance in the Development of Salatiga as a Creative City of Gastronomy - Dina, Sopia; Hadiwijoyo, Suryo Sakti; Fretes, Christian H.J de (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Gastronomy is not only related to food, but also encompasses cultural values, history, local identity, and community creativity. In the context of creative city development, gastronomy is considered a strategic sector as it can stimulate local economic growth, strengthen regional identity, and support sustainable tourism. Salatiga, a small city known as a